Primary Headache Disorder Among School Students in Kuwait - Shuaibi, Sameera; AlAshqar, Abdelrahman; Ahmed, Samar Farouk; Alroughani, Raed; AlThufairi, Hawraa; Owayed, Shaikhah; AlHamdan, Fajer; Al-Hashel, Jasem (Frontiers in Neurology, 2021)
Background: Primary headaches are remarkably prevalent worldwide and are increasingly reported among children. However, the exact trend in this age group, particularly in the Gulf region, remains largely unknown. Aims and Objectives: To examine the prevalence of primary headache disorders among primary and middle school students in Kuwait. Methods: We conducted a cross-sectional study that included Kuwaiti primary and middle school children and adolescents of both genders in randomly selected schools located in two governorates in Kuwait in the 2018/2019 academic year. Prevalence and attributable burden of headaches, definite and probable migraines, definite and probable tension-type headaches, chronic headaches (≥15 days/month), and probable medication-overuse headaches were assessed using the Headache-Attributed Restriction, Disability, Social Handicap, and Impaired Participation (HARDSHIP) questionnaire for children and adolescents. Results: Of 1,485 questionnaires that were distributed, 1,089 students completed the questionnaire with a respondent rate of 73.4%. The study population consisted of 420 boys (38.56%) and 669 girls (61.43%) students with a mean age of 11.5 ± 2.11 years. The 1-year prevalence of primary headache disorders was 42.78%, with more middle schoolers reporting headaches than primary schoolers (50.37 vs. 30.48%; p < 0.02). The mean age of students with primary headaches was 11.98 ± 2.03 years in both genders. When stratified according to diagnostic criteria, migraine headaches were the most frequently reported (20.75%), followed by tension type headaches (18.8%), chronic headaches (2.75%), and probable medication-overuse headaches (0.46%). Primary headaches were significantly higher in girls compared to boys among middle schoolers (66.46 vs. 38.49%; p < 0.001); however, no significant difference between genders was noted among primary school students (33.12 vs. 22.33%; p < 0.118). Conclusion: Primary headaches are remarkably common in Kuwaiti school students, with migraine headaches being the most frequently reported type. Age and female gender may play a role in the development of primary headaches. These findings necessitate the direction of health services and research efforts toward this age group and warrant the need for further epidemiological studies.